2010
DOI: 10.1007/s00125-010-1854-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate and albuminuria are independent predictors of cardiovascular events and death in type 2 diabetes mellitus: the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study

Abstract: Aims/hypothesis We investigated effects of renal function and albuminuria on cardiovascular outcomes in 9,795 lowrisk patients with diabetes in the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study. Methods Baseline and year 2 renal status were examined in relation to clinical and biochemical characteristics. Outcomes included total cardiovascular disease (CVD), cardiac and non-cardiac death over 5 years. Results Lower estimated GFR (eGFR) vs eGFR ≥90 ml min . CVD risk was further modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 52 publications
5
133
3
3
Order By: Relevance
“…Previous research showed that reduced eGFR is a risk factor of cardiovascular events and death in diabetes patients without advanced renal disease, but the risks are small when considering other risk factors 36. Although we found no association between renal impairment and outcomes in T2DM‐SAHF, such an association might become apparent with longer follow‐up.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous research showed that reduced eGFR is a risk factor of cardiovascular events and death in diabetes patients without advanced renal disease, but the risks are small when considering other risk factors 36. Although we found no association between renal impairment and outcomes in T2DM‐SAHF, such an association might become apparent with longer follow‐up.…”
Section: Discussioncontrasting
confidence: 78%
“…Supporting this notion, hazard ratios for all-cause mortality as well as cardiovascular mortality increased in normoalbuminuric diabetic patients with low GFR [19]. The FIELD study also revealed that normoalbuminuric patients with eGFR 30-59 ml/min per 1.73 m 2 had a higher risk of cardiovascular events, cardiovascular death, non-coronary heart disease deaths, death from any cause than normoalbuminuric patients with eGFR C60 ml/min per 1.73 m 2 [7]. Interestingly, in the ADVANCE study, patients with normoalbuminuria and eGFR \60 ml/min/1.73 m 2 had a 3.95-fold higher risk for renal events, a 1.33-fold higher risk for cardiovascular events and a 1.85-fold higher risk for cardiovascular death [6].…”
Section: \0001mentioning
confidence: 76%
“…A high urinary albumin-to-creatinine ratio (UACR) and low estimated glomerular filtration rate (eGFR) have been believed to be predictors for diabetic ESKD and death [5][6][7]. Kidney Disease Improving Global Outcomes (KDIGO) provided a new classification for chronic kidney disease (CKD) by adding stages that stratified urinary albumin excretion as well as eGFR and emphasizing clinical diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular complications start early in renal disease with even minor renal deterioration being associated with arterial thickening [7]. Current therapies may not arrest renal function decline and there is an urgent need for new targets and interventions [8], as renal failure and associated cardiovascular disease increase mortality rates [9]. Fenofibrate has been shown to decrease albuminuria in a mouse model of type 2 diabetes [10] and in humans [1,2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Greater preservation of estimated GFR with fenofibrate was observed with baseline hypertriacylglycerolaemia (n=169 vs 491 without) alone, or combined with low HDL-cholesterol (n=140 vs 520 without) and reductions of ≥0.48 mmol/l in triacylglycerol over the active run-in period (pre-randomisation) (n=356 vs 303 without). Fenofibrate reduced urine albumin concentrations and hence albumin/creatinine ratio by 24% vs 11% (p<0.001; mean difference 14% [95% CI [9][10][11][12][13][14][15][16][17][18]; p<0.001), with 14% less progression and 18% more albuminuria regression (p<0.001) than in participants on placebo. Endstage renal event frequency was similar (n=21 vs 26, p=0.48).…”
mentioning
confidence: 99%